Giant scaffolding protein AHNAK1 interacts with β‐dystroglycan and controls motility and mechanical properties of schwann cells. Issue 9 (3rd May 2014) - von Boxberg, Ysander; Soares, Sylvia; Féréol, Sophie; Fodil, Redouane; Bartolami, Sylvain; Taxi, Jacques; Tricaud, Nicolas; Nothias, Fatiha
<x xml:space="preserve">Abstract</x> The profound morphofunctional changes that Schwann cells (SCs) undergo during their migration and elongation on axons, as well as during axon sorting, ensheathment, and myelination, require their close interaction with the surrounding laminin‐rich basal lamina. In contrast to myelinating central nervous system glia, SCs strongly and constitutively express the giant scaffolding protein AHNAK1, localized essentially underneath the outer, abaxonal plasma membrane. Using electron microscopy, we show here that in the sciatic nerve of ahnak1−/− mice the ultrastructure of myelinated, and unmyelinated (Remak) fibers is affected. The major SC laminin receptor β‐dystroglycan co‐immunoprecipitates with AHNAK1 shows reduced expression in ahnak1−/− SCs, and is no longer detectable in Cajal bands on myelinated fibers in ahnak1−/− sciatic nerve. Reduced migration velocity in a scratch wound assay of purified ahnak1−/− primary SCs cultured on a laminin substrate indicated a function of AHNAK1 in SC motility. This was corroborated by atomic force microscopy measurements, which revealed a greater mechanical rigidity of shaft and leading tip of ahnak1−/− SC processes. Internodal lengths of large fibers are decreased in ahnak1−/− sciatic nerve, and longitudinal extension of myelin segments is even more strongly reduced after acute knockdown of AHNAK1 in SCs of developing sciatic nerve. Together, our results suggest that by interfering in the cross‐talk between the transmembrane form of the laminin receptor dystroglycan and F‐actin, AHNAK1 influences the cytoskeleton organization of SCs, and thus plays a role in the regulation of their morphology and motility and lastly, the myelination process. GLIA 2014;62:1392–1406